Comparison of cytokine/chemokine profiles between dermatomyositis and anti-synthetase syndrome - Wang, Yikang; Zheng, Yiming; Zhao, Yawen; Liu, Yilin; Zhang, Wenhao; Yu, Meng; Xie, Zhiying; Hao, Hongjun; Gao, Feng; Zhang, Wei; Wang, Zhaoxia; Yuan, Yun (Frontiers in Neurology, 2022)
Objectives: Dermatomyositis (DM) and anti-synthetase syndrome (ASS) are autoimmune diseases with multisystem involvement. Despite sharing some clinical and myopathological features, these are two diseases with different pathogenesis and prognosis. Our aims were to clarify and compare cytokine/chemokine profiles in both disorders, which may help in differential diagnosis. Materials and Methods: We collected clinical data and serum samples of consecutive DM and ASS patients. Quantibody® Human Inflammation Array 3 for cytokines/chemokines was performed in serum of all participants. Receiver operating characteristic analysis with area under the curve and Youden’s index were performed. Results: Eight newly diagnosed and treatment-naïve DM patients, nine newly diagnosed and treatment-naïve ASS patients and 14 healthy controls were enrolled. Serum C-C motif chemokine ligand (CCL) 2, CCL4, C-X-C motif chemokine ligand (CXCL) 13 and TNF receptor 2 (TNFR2) were increased in both DM and ASS patients. Serum interleukin (IL)-1 receptor type 1 (IL-1ra), IL-1b, CCL1, CXCL11, CCL3 were modulated in DM patients only, and IL-8, CXCL9 and tissue inhibitor of metalloproteinases-1 (TIMP-1) in ASS patients only. Serum CCL2, CXCL13 and TNFR2 accurately distinguished DM and ASS patients from healthy controls, as shown by area under the curve > 0.80. Moreover, receiver operating characteristic analysis showed that, as biomarkers for discrimination between DM and ASS, the combination of IL-1ra and TIMP-1, had an area under the curve of 0.944, a sensitivity of 87.5%, and a specificity of 88.9%. Conclusion: Our study demonstrated that serum levels of cytokines/chemokines showed different pattern in newly diagnosed DM and ASS patients, in which serum IL-1ra and TIMP-1 could be used to distinguish between the two diseases.